Where River Meets the Sea: Participatory Water Management in Coastal Bangladesh. (April 2017) - Buisson, Marie-Charlotte; Das, Arijit; Mukherji, Aditi
Regular supply of maintenance fund for water infrastructures in costal Bangladesh is a necessary condition for the existence of river embankments. This article reviews a number of efforts to identify rules and conditions helping the regular supply of maintenance fund. A number of studies have used experimental games to replicate a real-life situation. The experimental results show that participants from Local Government Engineering Department polders significantly contribute more than players from Bangladesh Water Development Board polders which indicate importance of institutional environment. Also, our study finds significant importance of economic homogeneity in the group as well as proportional sharing of benefits increases the level of contribution. JEL: C93, Z13, D74